THE INFLUENCE OF CREDIBILITY AND ATTRACTIVENESS OF BEAUTY VLOGGER AS A CELEBRITY ENDORSER ON CONSUMER PURCHASE INTENTION - Hikmawati Hikmawati (Universitas muhammadiyah malang, 2019)
This study aims to identify the effect of beauty vlogger’s credibility and attractiveness on purchase intention and find the most influential variable. A quantitative approach using survey (questionnaire) was used. The population in this study was 41.517 viewers of Abel Cantika's vlog titled